Relaxation Technique of Deep Breathing In Post- Appendectomy Patients: A Case Study - Nasrullah, Nasrullah; SULASRI, SULASRI; HASBULLAH, HASBULLAH; RARA, ABD RAHMAN; MANANOHAS, MAUREEN GRACE (PT.Mantaya Idea Batara, 2024)
Appendicitis is a condition characterized by inflammation of the appendix. While mild cases may resolve without treatment, many require surgical removal of the infected appendix through a procedure known as laparotomy. Post-appendectomy pain can significantly impact daily activities, including rest, sleep, and personal well-being. Severe pain, if not addressed promptly with non- pharmacological interventions, can lead to neurogenic shock. Methods: This study employed a descriptive case study approach to investigate the effectiveness of deep breathing relaxation techniques in managing post-appendectomy pain. Results: The study involved two respondents who underwent deep breathing relaxation exercises twice daily for 15 minutes over three days. The results showed a decline in pain intensity for both respondents. Respondent 1 experienced a reduction from moderate pain (score of 3) to mild pain (score of 2), while Respondent 2's pain intensity decreased to moderate pain (score of 3). Conclusion: The findings suggest that deep breathing exercises and relaxation techniques can be beneficial in reducing pain levels in post-appendectomy patients when practiced consistently over a period of time.